THE PROBLEM OF BULLING IN THE MODERN EDUCATIONAL ENVIRONMENT AND THE WAYS OF ITS OVERCOMING - Sorochuk, Liudmyla (Київський національний університет імені Тараса Шевченка, 2019)
The problem of the emergence of bullying in the educational area among school-age children is investigated, since in recent years in Ukraine the bullying (baiting) has often been referred to as a negative phenomenon. A brief analysis of modern scientific investigations on the problems of bullying in the educational environment is done, which shows the necessity of a detailed and systematic study on this problem. Bulling is seen as a conflict and widespread phenomenon in children's groups, which can cause a negative impact on formation of personality, difficulties in socio-psychological adaptation, complexity and uncertainty of a young person in choice of next career. It has been noted that numerous facts of child abuse have caused attention to this phenomenon and implementation of specific steps at the state level to counteract and prevent this problem. It is emphasized that the presence of bullying in the educational environment has a negative impact not only on the victim of persecution, but also on the perpetrators (abusers, observers) as well as on parents and teachers. Emphasis is placed on the necessity of coordinated work of educational institutions, school psychologists, social educators, lawyers, parents to overcome bullying, which, respectively can reduce the manifestation of this negative phenomenon and greatly improve the resolution of conflict situations. Finding peaceful ways to resolve conflict situations, upbringing of friendly relationships between children and assimilate moral values leads to a healthy psychological climate in the children's groups, educate the respect and mutual assistance among coevals. There are a number of methodological recommendations for organizing the educational process, conducting cultural events, leisure, extracurricular work, outdoor activities, which help to prevent such a negative phenomenon of our reality. It is concluded that the joint work of relevant state institutions, educators, lawyers, psychologists, parents, media representatives, using different methods of influence on the individuals, may provide conditions for resolution of conflicts and overcoming bullying among children and school youth.

Досліджується проблема виникнення булінгу в освітньо-виховному просторі серед дітей шкільного віку, адже впродовж останніх років в Україні часто почали говорити про булінг (цькування) як про негативне явище. Зроблено короткий аналіз сучасних наукових розвідок, присвячених проблемам булінгу в освітньому середовищі, що засвідчує необхідність детального й систематичного вивчення зазначеного питання. Булінг розглядається як конфліктне й широко розповсюджене явище в дитячих колективах, яке може викликати негативний вплив на формування особистості, важку соціально-психологічну адаптацію, закомплексованість та невизначеність життєвого вибору молодої людини. Зазначено, що численні факти проявів дитячого насильства стали причиною привернення уваги до цього явища й здійснення на державному рівні конкретних кроків щодо протидії та запобігання даній проблемі. Наголошено на тому, що наявність булінгу в освітньому середовищі, має негативний вплив не лише на жертву цькування, а також на винуватців (кривдників, спостерігачів), на батьків та педагогів. Акцентується увага на злагодженій роботі працівників освітніх закладів, шкільних психологів, соціальних педагогів, юристів, батьків, щодо подолання булінгу, що, відповідно, може привести до зменшення проявів цього негативного явища й значно покращує вирішення конфліктних ситуацій. Пошук мирних шляхів розв’язання суперечливих питань, виховання дружніх взаємин між дітьми та засвоєння моральних цінностей спонукає до здорового психологічного клімату в дитячому колективі, виховання поваги та взаємодопомоги між ровесниками. Наводиться цілий ряд методичних рекомендацій щодо організації навчально-виховного процесу, проведення культурних заходів, дозвілля, позакласної роботи, активного відпочинку, що допомагає запобіганню такого негативного явища в нашій реальній дійсності.
ПРОБЛЕМА БУЛІНГУ В СУЧАСНОМУ ОСВІТНЬО-ВИХОВНОМУ СЕРЕДОВИЩІ ТА ШЛЯХИ ЇЇ ПОДОЛАННЯ
Keywords: bullying; aggressive behavior; moral and physical harm; seclusion; conflict management; selfesteem; counteraction to bullying; булінг; агресивна поведінка; моральна та фізична шкода; замкнутість; врегулювання конфліктної ситуація; самооцінка; протидії булінгу